2016
DOI: 10.1017/jse.2016.7
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Students With Autism Spectrum Disorder in Research Through Participant-Driven Photo-Elicitation Research Technique

Abstract: Participant-driven photo-elicitation, a visual research technique, is commonly used with marginalised and vulnerable groups of individuals. Reflections on the use of this technique are illustrated through a study examining the conceptualisation of student wellbeing from the perspectives of teachers, parents, and students with autism spectrum disorder. Interviews were used to collect data from teachers and parents, while photovoice, a community and participatory action research strategy, was used as a data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…Beresford et al 2004;Preece 2002) as well as more recent work (e.g. Danker, Strnadová & Cumming 2017;Ellis 2016) have made important contributions to our understanding of how to engage children 4 with autism in research: for example researchers have suggested using visual stories to help the young people understand and prepare themselves for the research process (Beresford et al 2004;Harrington et al 2014), focussing the conversation on concrete experiences (Beresford et al 2004;Preece & Jordan 2010), and using craft-making activities or photographs as a creative focus to engage the young people practically in the session (Beresford et al 2004;Danker et al 2017;Ellis 2016;Loyd 2015;Shepherd 2015). However, what remains unclear is a more detailed picture of which approaches, methods and techniques may help support meaningful research interactions with younger people and children with autism, and how researchers can ethically and respectfully respond to the dilemmas and opportunities that occur in their research.…”
Section: Giving Voice and Meaningful Encountersmentioning
confidence: 83%
“…Beresford et al 2004;Preece 2002) as well as more recent work (e.g. Danker, Strnadová & Cumming 2017;Ellis 2016) have made important contributions to our understanding of how to engage children 4 with autism in research: for example researchers have suggested using visual stories to help the young people understand and prepare themselves for the research process (Beresford et al 2004;Harrington et al 2014), focussing the conversation on concrete experiences (Beresford et al 2004;Preece & Jordan 2010), and using craft-making activities or photographs as a creative focus to engage the young people practically in the session (Beresford et al 2004;Danker et al 2017;Ellis 2016;Loyd 2015;Shepherd 2015). However, what remains unclear is a more detailed picture of which approaches, methods and techniques may help support meaningful research interactions with younger people and children with autism, and how researchers can ethically and respectfully respond to the dilemmas and opportunities that occur in their research.…”
Section: Giving Voice and Meaningful Encountersmentioning
confidence: 83%
“…Photo elicitation is a form of Photovoice whereby photos can be archival (already taken) or generated by a non-participant to elicit conversation (e.g. Danker, Strnadová, & Cumming, 2017) as a facilitation technique. Photovoice and photo elicitation within our identified studies were common strategies applied to elicit the first-person perspectives of youth with disabilities such as ASD (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Photovoice and photo elicitation within our identified studies were common strategies applied to elicit the first-person perspectives of youth with disabilities such as ASD (e.g. Danker et al, 2017; Ha & Whittaker, 2016; Hill, 2014; Obrusnikova & Cavalier, 2011; Teti, Cheak-Zamora, Lolli, & Maurer-Batjer, 2016). These photo methods have been proposed as engaging tools to elicit the perspectives of youth, particularly those with speech and communication impairments, as they rely less on verbal responses (Aldridge, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Only parents and teachers of students with autism and intellectual disabilities were interviewed. Future research needs to consider including the voices of students with autism and intellectual disabilities themselves by using accessible research methods, such as photovoice (Danker, Strnadová, & Cumming, 2017). Furthermore, exploring transition planning and procedures across all states in Australia would allow for more in-depth understanding, especially in light of a rather recent call for making transition planning practices mandatory (New South Wales Parliament, Legislative Council, Standing Committee on Social Issues, 2012).…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%